New insights into mechanical, metabolic and muscle oxygenation signals during and after high-intensity tethered running - Manchado-Gobatto, F. B.; Marostegan, A. B.; Rasteiro, F. M.; Cirino, C.; Cruz, J. P.; Moreno, M. A.; Gobatto, C. A. (Scientific Reports, 2020)
High-intensity exercises including tethered efforts are commonly used in training programs for athletes, active and even sedentary individuals. Despite this, the knowledge about the external and internal load during and after this effort is scarce. Our study aimed to characterize the kinetics of mechanical and physiological responses in all-out 30 seconds (AO30) tethered running and up to 18 minutes of passive recovery. Additionally, in an innovative way, we investigated the muscle oxygenation in more or less active muscles (vastus lateralis and biceps brachii, respectively) during and after high-intensity tethered running by near-infrared spectroscopy - NIRS. Twelve physically active young men were submitted to AO30 on a non-motorized treadmill to determine the running force, velocity and power. We used wearable technologies to monitor the muscle oxygenation and heart rate responses during rest, exercise and passive recovery. Blood lactate concentration and arterial oxygen saturation were also measured. In a synchronized analysis by high capture frequency of mechanical and physiological signals, we advance the understanding of AO30 tethered running. Muscle oxygenation responses showed rapid adjustments (both, during and after AO30) in a tissue-dependence manner, with very low tissue saturation index observed in biceps brachii during exercise when compared to vastus lateralis. Significant correlations between peak and mean blood lactate with biceps brachii oxygenation indicate an important participation of less active muscle during and after high-intensity AO30 tethered running.